PENGARUH DEBT TO EQUITY RATIO, CURRENT RATIO, DAN TOTAL ASSET TURNOVER TERHADAP ROA (Studi Empiris Pada Perusahaan LQ 45 Non Bank Yang Terdaftar Di Bursa Efek Indonesia) - Dewi Prastika Arum, 12.05.52.0101; Susilowati, Yeye (Students' Journal of Accounting and Banking, 2017)
This study examined the effect of Debt to Equity Ratio, Current Ratio, and Total Asset Turnover on Return On Assets. Iini research done at the Indonesian Stock Exchange with the unit of analysis Non Bank LQ45 companies that have gone public. The sampling method using purposive sampling method with the period of the study, 2011 to 2014 or influence the relationship between variables is described using multiple regression analysis. The test results variable Debt to Equity Ratio (DER) significant negative effect on ROA, while the Current Ratio (CR), and Total Asset Turnover (TAT) significant positive effect on ROKeywords: ROA, ROE, DER, CR, and TAT